ANALISIS KEBUTUHAN MATERI KIMIA UNTUK SISWA SMK KOMPETENSI KEAHLIAN AGRIBISNIS PERIKANAN AIR PAYAU DAN LAUT - Sultan Hadi Prabowo, - (2022)
Penelitian ini dilatarbelakangi oleh kurang tersedianya bahan ajar kimia yang relevan untuk menunjang penguasaan kompetensi siswa pada mata pelajaran kejuruan SMK kompetensi keahlian Agribisnis Perikanan Air Payau dan Laut (APAPL). Materi kimia yang terdapat dalam bahan ajar kimia SMK keahlian APAPL masih bersifat umum dan tidak dihubungkan dengan konteks keahlian APAPL, sehingga fungsi mata pelajaran kimia sebagai mata pelajaran adaptif belum terpenuhi. Penelitian ini bertujuan untuk menghasilkan kebutuhan materi kimia untuk siswa SMK kompetensi keahlian APAPL sebagai dasar untuk memperoleh outline bahan ajar kimia. Outline bahan ajar kimia ini dapat dijadikan acuan untuk mengembangkan bahan ajar kimia di SMK kompetensi keahlian APAPL. Desain penelitian yang digunakan adalah Research and Development (R&D) dengan pendekatan kualitatif. Partisipan dalam penelitian ini terdiri dari satu guru kimia SMK dan enam guru kejuruan APAPL. Data diperoleh melalui wawancara dan reviu dengan guru kimia dan guru kejuruan APAPL. Hasil penelitian menunjukkan bahwa (1) materi kimia adaptif tidak sesuai dengan kebutuhan materi kejuruan di APAPL, (2) terdapat materi kimia lain yang dapat menunjang materi kejuruan di APAPL yaitu makromolekul yang berkaitan dengan mata pelajaran Produksi Pakan Alami dan Buatan serta pengenalan ilmu kimia yang berkaitan dengan semua mata pelajaran kejuruan di APAPL, (3) ruang lingkup materi kimia di APAPL dirinci sesuai dengan urutan penyajian dan konteks keahlian yang dibutuhkan siswa di APAPL dalam bentuk outline bahan ajar. Materi kimia yang dibutuhkan di APAPL setelah melalui proses analisis materi prasyarat yaitu berjumlah empat belas materi kimia. Outline bahan ajar ini berguna untuk kemudian dikembangkan oleh peneliti lain menjadi bahan ajar kimia untuk kompetensi keahlian APAPL. This research is motivated by the lack of availability of relevant chemistry teaching materials to support student competencies in vocational subjects of brackishwater and seawater fishery agribusiness. The chemistry subject on brackishwater and seawater fishery agribusiness materials is still in general approach, unlike the one in brackishwater and seawater fishery agribusiness expertise. Therefore, the function of chemistry subject as an adaptive subject has not been fulfilled. This study aims to analyze the need for chemistry teaching materials for vocational high school students with brackishwater and seawater fishery agribusiness expertise competencies as a basis for obtaining an outline of chemistry teaching materials. The outline of these chemistry teaching materials can be used as a reference for developing chemistry teaching materials for vocational high school students with brackishwater and seawater fishery agribusiness expertise competencies. The research design used is Research and Development (R&D) with qualitative approaches. Participants in this study consisted of one vocational chemistry teacher and six vocational teachers with brackishwater and seawater fishery agribusiness expertise competencies. Data were obtained through interviews with chosen participants. The results showed that (1) chemistry teaching materials were not under accordance with the needs of vocational materials in brackishwater and seawater fishery agribusiness expertise competencies, (2) there are other chemistry teaching materials that can support vocational materials in brackishwater and seawater fishery agribusiness, namely macromolecules related to the subject of Natural and Artificial Feed Production and the introduction of chemistry related to all vocational subjects in brackishwater and seawater fishery agribusiness, (3) the scope of chemistry teaching material in brackishwater and seawater fishery agribusiness is detailed according to the order of presentation and context of skills required by students in the form of teaching materials outline. The chemistry teaching materials needed in brackishwater and seawater fishery agribusiness after going through the prerequisite material analysis process are fourteen chemistry materials. This outline of teaching materials can be used to develop student competencies in vocational subjects of brackishwater and seawater fishery agribusiness.